Anesthetic Management for EC-IC Bypass Procedure in a Patient with Fontan Physiology: Navigating a Vascular Multimorbidity - Thakur, Nimisha; Ghosh, Sohini; Goraksha, Shwetal (Journal of Neuroanaesthesiology and Critical Care, 2025)
The Fontan procedure is a palliative procedure that reduces mortality associated with complex congenital cardiac anomalies. With advanced surgical techniques and improved perioperative care, an increase in the survival rate of palliated complex heart disease patients is rightfully expected. These patients may be encountered in noncardiac surgical suites and require special considerations. We present an interesting case of a 34-year-old male with a rare combination of vascular anomalies in the form of Fontan physiology and moyamoya disease with secondary polycythemia, posted for extracranial-intracranial bypass. We describe the perioperative management of this patient, maintaining stable hemodynamic on dual fronts, avoiding compromise in pulmonary circulation under positive pressure ventilation (a consideration in Fontan physiology), as well as cerebral ischemic complications (known risk with moyamoya disease). Only one case has been reported so far with a similar combination of vascular multimorbidity, in a patient, who underwent pial synangiosis.
Keywords: moyamoya disease; Fontan physiology; combined vascular morbidities